Asesmen Potential Review pada Karyawan Rumah Sakit Islam YY Pekanbaru - Abdullah Adhha; Dian Fithriwati Darusmin (Psyche 165 Journal, 2021)
Human Resources are assets that are needed for an organization, both those engaged in services and in the field of production goods. Every organization will certainly have the potential of human resources that are different from one another. This is a challenge for the organization to find and map the potential of its human resources, so we need an alternative that can be used to find potential employees owned by an organization or known as potential review. This study aims to measure the potential capacity of employees who are following the performance evaluation process so that they can identify the hospital's needs in employee self-development. In addition, the purpose of this study is to provide recommendations and suggestions for interventions that are in accordance with the results of the assessment in order to help optimize employee performance. Subjects in this study amounted to 1 person who is in the position of Cashier Supervisor. Methods of data collection using psychological tests and interviews. Data analysis used descriptive analysis and qualitative analysis. The results of the assessment show that the subject meets the potential standards that are expected to fill the Cashier Supervisor position with recommendations that can still be developed to occupy the Hospital Cashier Supervisor position so that later they can maximize their potential in carrying out the tasks and responsibilities given. In conclusion, a potential review assessment for the Cashier Supervisor position is needed to be carried out in the development of human resources through Coaching to develop the potential of the Subject's leadership abilities in order to carry out the functions, duties, and responsibilities as a leader in the cashier work unit